Analysis of full-wafer size co-diffused BCBJ silicon solar cells with a novel screen printed boron-doping paste. (September 2017) - Huyeng, Jonas D.; Efinger, Raphael; Spribille, Alma; Keding, Roman; Doll, Oliver; Clement, Florian
Abstract: This work presents an analysis of co-diffused back-contact back-junction silicon solar cells, fabricated by utilizing screen printed boron-doping paste. The feasibility of this paste has been shown in earlier work by the authors. Due to its promising performance, comparable to earlier used boron-doped silicate glass coatings, a proof-of-principle cell run was performed yielding, several small devices with various unit cell geometries and full-wafer size devices. The achieved mean conversion efficiency of nine small devices was η = 20.9 %, while the best full-wafer size device achieved η = 20.6 %. The cells are analyzed with a focus on the significant difference between small and large cells in short circuit density (Δ J SC = -4%) and the current limitations of the built cells assessed by numerical simulations. A set of improved parameters derived from earlier work at Fraunhofer ISE suggests an efficiency potential exceeding η = 23 %. The short- and long-term measures necessary to realize this potential are described in this paper.